Synergistic Impact of High-Fat Diets and Smoking on Cardiovascular Health: A Literature Review - Permatasari, Zendy Indah; Rohman, Muhammad Chabibur; Sabilla, Virina Dwi; Rahmawati, Laili; Khoiriyah, Romyun Alvy (International Conference on Sustainable Health Promotion, 2025)
Cardiovascular disease continues to be a global public health challenge with multiple complex risk factors. The combination of high-fat diet and smoking habits has a synergistic effect that increases the risk of cardiovascular disease. This study aimed to determine the relationship between a high-fat diet and smoking habits and cardiovascular disease, and to emphasize the importance of dual interventions targeting dietary changes and smoking cessation as the primary strategy to reduce the burden of coronary heart disease and stroke. This study used a literature review method. The results of this study indicate that smoking and excessive fat consumption are two major risk factors contributing to the increasing incidence of cardiovascular disease (CVD). Smoking has been shown to accelerate the process of atherosclerosis by increasing blood pressure, vascular inflammation, and decreasing HDL cholesterol levels. Consuming saturated fat makes this condition worse by raising levels of easily oxidized LDL cholesterol and lowering levels of HDL cholesterol, which speeds up the accumulation of plaque in blood vessels.  Nutritional interventions like lowering saturated fat and raising MUFA intake through a nutritious diet, like the Mediterranean diet, can lower this risk.  This all-encompassing approach is anticipated to dramatically lower the incidence of coronary heart disease in at-risk groups when paired with smoking cessation initiatives.